Positive Perceptions, Entrepreneurial Self-Efficacy, and Agripreneurial Interest Among Generation Z: Evidence from Indonesia - Alfin Nur Arifah; Aditia Abdurachman; Indri Febriyanti (School of Business, IPB University (SB-IPB), 2026)
Background: Agricultural regeneration in developing economies depends critically on youth engagement, yet Generation Z participation in agripreneurship remains constrained by psychological barriers and structural gaps. Although perception and self-efficacy are recognized determinants of entrepreneurial intention, their interaction specifically the moderating role of entrepreneurial self-efficacy remains underexplored in agripreneurship research, particularly in the Indonesian context.Purpose: (1) examining the direct effects of agricultural perception and entrepreneurial self-efficacy on Gen Z's agripreneurial interest, (2) testing entrepreneurial self-efficacy as a moderating variable in the perception–intention relationship, and (3) generating empirical evidence applicable to youth agripreneurship development in the Indonesian context an emerging economy where such integrative psychological models remain scarce.Design/methodology/approach: A convergent mixed-methods design was employed. Quantitative data from 138 purposively sampled Generation Z respondents in West Java were analyzed using Structural Equation Modelling–Partial Least Squares (SEM-PLS) via SmartPLS 4. Qualitative data were collected through in-depth interviews with 10 young agripreneurs and a Focus Group Discussion (FGD) with YESS program stakeholders, analyzed via thematic analysis.Findings: Perception significantly and positively influences agripreneurial interest (β = 0.513, p < 0.001). Self-efficacy also exerts a positive direct effect (β = 0.468, p < 0.001). Notably, self-efficacy negatively moderates the perception–intention relationship (β = −0.048, p = 0.043), indicating that excessively high self-confidence may attenuate the motivational impact of positive perceptions by inducing more critical appraisals of agribusiness challenges. The model explains 78.7% of variance in agripreneurial interest (R² = 0.792). Qualitative findings validate these results and highlight institutional barriers limited capital, unstable markets, and technology gaps alongside the facilitative role of the YESS program.Conclusion: Agricultural perception and entrepreneurial self-efficacy are significant co-drivers of Generation Z's agripreneurial interest, with self-efficacy functioning as a compensatory moderator findings that extend Social Cognitive Theory to the agripreneurship domain and provide an empirically grounded framework for redesigning youth agripreneurship interventions, particularly in sustaining the legacy of Indonesia's YESS program beyond its formal conclusion in 2025.Originality/value: This study extends Social Cognitive Theory to the agripreneurship domain by introducing entrepreneurial self-efficacy as a moderating variable a theoretical innovation rarely examined in Southeast Asian agricultural entrepreneurship research. The mixed-methods design further enriches empirical validity and contextual depth. Keywords: generation Z, agricultural entrepreneurship, perception, entrepreneurial self-efficacy, youth agripreneurship, SEM-PLS, Indonesia